The StoNED Age: The Departure Into a New Era of Efficiency Analysis? – A Monte Carlo Comparison of StoNED and the "Oldies" (SFA and DEA) - Mark Andor; Frederik Hesse (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2013)
Based on the seminal paper of Farrell (1957), researchers have developed several methods for measuring effi ciency. Nowadays, the most prominent representatives are nonparametric data envelopment analysis (DEA) and parametric stochastic frontier analysis (SFA), both introduced in the late 1970s. Researchers have been attempting to develop a method which combines the virtues - both nonparametric and stochastic - of these 'oldies'. The recently introduced Stochastic non-smooth envelopment of data (StoNED) by Kuosmanen and Kortelainen (2010) is such a promising method. This paper compares the StoNED method with the two 'oldies' DEA and SFA and extends the initial Monte Carlo simulation of Kuosmanen and Kortelainen (2010) in several directions. We show, among others, that, in scenarios without noise, the rivalry is still between the 'oldies', while in noisy scenarios, the nonparametric StoNED PL now constitutes a promising alternative to the SFA ML. – – Basierend auf dem bahnbrechenden Artikel von Farrell (1957) haben Forscher zahlreiche Methoden zur Effizienzschätzung entwickelt. Die populärsten Methoden sind aktuell die nicht-parametrische Data Envelopment Analysis (DEA) und die parametrische Stochastic Frontier Analysis (SFA), welche beide Ende der 1970er Jahre eingeführt wurden. Forscher haben seitdem versucht eine Methode zu entwickeln, die die Vorzüge der 'Oldies' kombiniert. Die vor kurzem von Kuosmanen und Kortelainen (2010) eingeführte Stochastic Non-smooth Envelopment of Data (StoNED) Methode ist so eine vielversprechende Methode. Dieser Artikel vergleicht die StoNED Methode mit den beiden 'Oldies' - DEA und SFA - und erweitert dabei die initiale Monte Carlo Simulation von Kuosmanen und Kortelainen (2010) in verschiedene Richtungen. Es wird unter anderem gezeigt, dass in Szenarien ohne stochastische Einflüsse weiterhin die 'Oldies', DEA und SFA, die besten Ergebnisse liefern, während in Szenarien mit stochastischen Einflüssen die semi-parametrische StoNED eine vielversprechende Alternative zur SFA darstellt.
Keywords: C1; C5; D2; L5; Q4; 330; efficiency; stochastic non-smooth envelopment of data (StoNED); data envelopment analysis (DEA); stochastic frontier analysis (SFA); Monte Carlo simulation